∫ 0 ∞ 4 x 2 + 1 cos ( π x ) d x = B 1 π e A − π
The equation above holds true for some positive integers A and B . Find A + B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Cauchy Integral Formula
Since the integrand is even, we have ∫ 0 ∞ 4 x 2 + 1 cos ( π x ) d x = 2 1 ∫ − ∞ ∞ 4 x 2 + 1 cos ( π x ) d x . We can solve this integral by using the closed contour C of a semicircle of radius R → ∞ in the upper half of the complex plane.
Therefore the integral is as follows:
∫ C 4 z 2 + 1 e i π z d z = ∫ − R R 4 z 2 + 1 e i π z d z + ∫ a r c 4 z 2 + 1 e i π z d z = ∫ − ∞ ∞ 4 x 2 + 1 cos π x d x Note that R → ∞ lim ∫ a r c 4 z 2 + 1 e i π z d z = 0
Therefore, we have:
⟹ ∫ 0 ∞ 4 x 2 + 1 cos ( π x ) d x = 2 1 ∫ C 4 z 2 + 1 e i π z d z = 8 1 ∫ C z 2 + 4 1 e i π z d z = 8 1 ∫ C ( z − 2 i ) ( z + 2 i ) e i π z d z = 8 1 ⋅ 2 π i ⋅ ( 2 i + 2 i ) e i π ⋅ 2 i d z = 4 1 π e − 2 π Only pole within contour z = 2 i By Cauchy integral formula
⟹ A + B = 2 + 4 = 6
(+1) for drawing the contour and amazing latex work.
Using residue theorem is some time ago for me. Thanks for refreshing memory!
Hello sir. Integration Contest 3 is ongoing. I'd like to invite you to participate :)
Inside Complex Analysis, supposing known residue theorem...
Proposition 1.-
Let P , Q be polynomials with degree (Q) - degree (P) ≥ 1 . If f = Q P doesn't have any poles at the real axis, the following improper integral converges and its value is ∫ − ∞ ∞ f ( x ) ⋅ e i x d x = 2 i π ⋅ I m a > 0 ∑ Res( f ( x ) ⋅ e i x , a ) with a being a pole of f .
Proof .-
(Only if someone asks to me)
Examples.- Let a , b ∈ R such that a , b > 0
I = ∫ 0 ∞ t 2 + a 2 cos b t d t = 2 a e a b π J = ∫ 0 ∞ t 2 + a 2 t sin b t d t = 2 e a b π
Proof.-
I , J are integrals of even functions,
Calculation of I:
I = ∫ 0 ∞ t 2 + a 2 cos b t d t = 2 b ( ∫ − ∞ ∞ x 2 + a 2 b 2 cos x d x ) = 2 b ( Real ∫ − ∞ ∞ x 2 + a 2 b 2 e i x d x ) then we are going to apply proposition 1. The only pole of x 2 + a 2 b 2 e i x in the upper-half plane is z = a b i and its residue value is 2 a b i e − a b so ∫ − ∞ ∞ x 2 + a 2 b 2 e i x d x = 2 π i 2 a b i e − a b = a b e a b π ⇒ I = 2 a e a b π . With this we can calculate the above integral, (for instance like Isan Signh did ), this is A = 2 , B = 4
Calculation of J:
J = ∫ 0 ∞ t 2 + a 2 t sin b t d t = 2 1 ( ∫ − ∞ ∞ x 2 + a 2 b 2 x sin x d x ) = 2 1 ( Image ∫ − ∞ ∞ x 2 + a 2 b 2 x e i x d x ) then we are going to apply proposition 1. The only pole of x 2 + a 2 b 2 x e i x in the upper-half plane is z = a b i and its residue value is 2 e − a b so ∫ − ∞ ∞ x 2 + a 2 b 2 x e i x d x = 2 π i 2 e − a b = e a b π i ⇒ J = 2 e a b π □
Proposition 2.- (for Refaat..)
Let P , Q be polynomials with degree (Q) - degree (P) ≥ 1 . If f = Q P doesn't have any poles at the real axis, except at the origin, where f is able to have a simple pole. Then, ∀ ϵ > 0 , the integrals ∫ − ∞ − ϵ f ( x ) ⋅ e i x d x , ∫ ϵ ∞ f ( x ) ⋅ e i x d x converge as ϵ → 0 , and ϵ → 0 lim ∫ ∣ x ∣ ≥ ϵ f ( x ) ⋅ e i x d x = 2 i π ⋅ I m a > 0 ∑ Res( f ( x ) ⋅ e i x , a ) + i π ⋅ Res( f ( x ) ⋅ e i x , 0 )
( Proof.- Only if Refaat asks to me, because this proposition is not necessary for this exercise)
Example.-
∫ 0 ∞ t sin t d t = 2 π
Proof.-
Applying proposition 2, Res ( x e i x , 0 ) = 1 ⇒ ∫ − ∞ ∞ x e i x d x = π i ⇒ ∫ 0 ∞ x sin x d x = 2 π
Of course you can post your solution. But we will not apply the corollary in this problem . You know why?
Log in to reply
do you mean because that corollary use e i x ?(That has easy fixing) or what do you want to say?Now, I don't understand you very good... Then, do you want me to write the solution? and you fix my mistakes and ask me your doubts?
Log in to reply
No we won't use the corollary because the roots of the function not real. Any way, you can post the solution and we check it together
Log in to reply
@Refaat M. Sayed – ok, I'll start very soon, but Isan Sighn has just posted one solution... And he gets the same than me... Anyway, I'll post the corollary and I'll make than I am able to do... I haven't read his solution... maybe it's very similar than mine... In two hours, I hope to start with the corollary and proving his proposition with this corollary of residue theorem...
Log in to reply
@Guillermo Templado – I have "finished" this proof... Then, please could you tell me your doubts in this problem and in the other problem(because I'm pretty certain than you have some doubt, at least in the other problem), my mistakes, suggestions? do you want me to make the proofs of propositions 1 and 2?, Good, etc, etc...
Log in to reply
@Guillermo Templado – (+1) from me. Excellent analysis @Guillermo Templado . Good work ⌣ ¨
Log in to reply
@Refaat M. Sayed – thank you very much, (+1) in Likes...
Hello sir. Integration Contest 3 is ongoing. I'd like to invite you to participate :)
Log in to reply
Please, don't cal me sir, buddy, I know I'm not young, but I prefer buddy, friend,... thank you anyway. I don't know... I don't contest now, but I'll see this web and what I'll do, althought my methods are old like me, ;) :)...
For variety... Taking the Fourier transform of the function f ( x ) = e − 2 1 ∣ x ∣ , ( F f ) ( t ) = 2 π 1 ∫ R f ( x ) e − i x t d x = 2 π 1 ( 2 1 + i t 1 + 2 1 − i t 1 ) = π ( 4 t 2 + 1 ) 2 2 and so (the function f is well-behaved for this identity to be true for all x , and not just in the "almost everywhere" sense) f ( x ) = ( F − 1 F f ) ( x ) = 2 π 1 ∫ R ( F f ) ( t ) e i t x d t = π 2 ∫ R 4 t 2 + 1 e i t x d t so that ∫ 0 ∞ 4 t 2 + 1 cos π t = 2 1 ∫ R 4 t 2 + 1 e i π t d t = 4 1 e − 2 1 π making the answer 2 + 4 = 6 .
Hello sir. Integration Contest 3 is ongoing. I'd like to invite you to participate :)
Used the same approach; I find this approach truly elegant.
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Differentiation Under the Integral Sign
Proof :
I ( m ) = ∫ 0 ∞ x 2 + a 2 cos m x d x ( 1 )
Using Integration by parts,
I ( m ) = ∫ 0 ∞ m ( x 2 + a 2 ) 2 2 x sin m x d x
⟹ m ⋅ I ( m ) = ∫ 0 ∞ ( x 2 + a 2 ) 2 2 x sin m x d x ( 2 )
Partially Differentiating ( 2 ) w.r.t. m , we have,
I + m ∂ m ∂ I = ∫ 0 ∞ ( x 2 + a 2 ) 2 2 x 2 cos ( m x ) d x = ∫ 0 ∞ ( x 2 + a 2 ) 2 cos ( m x ) d x − 2 a 2 ∫ 0 ∞ ( x 2 + a 2 ) 2 cos m x d x
⟹ m ∂ m ∂ I = I − 2 a 2 ∫ 0 ∞ ( x 2 + a 2 ) 2 cos m x d x ( 3 )
Again, partially differentiating ( 3 ) w.r.t. m , we have,
m ∂ m 2 ∂ 2 I = a 2 ∫ 0 ∞ ( x 2 + a 2 ) 2 2 x sin m x d x
\implies \dfrac{\partial^2}{\partial m^2} \text{I} = a^2 \text{I} \tag{*} (from ( 2 ) )
Note that I ( 0 ) = 2 a π and I ( ∞ ) = 0
Now, solving ( ∗ ) , we have,
I = 2 a π e − a m
0 ∫ ∞ 4 x 2 + 1 cos ( π x ) d x = 4 1 0 ∫ ∞ x 2 + 4 1 cos ( π x ) d x = 4 π e − 2 π
⟹ A + B = 6